+0  
 
0
360
1
avatar

1. Simplify Each of the following:

a. the sum of 6x + 2 and -8x + 5

b. the result of subtracting 5x - 17 from 8x + 12

c. the product of 7x and 4x - 9

 

2. Solve 2/3 (3x + 14) = 7x + 6, by the first multiplying both sides of the equation by 3, before applying the distributive property.

 

Thanks!

Guest Apr 15, 2017
 #1
avatar+92622 
+2

1.

a.

 6x + 2 - 8x + 5   =

6x - 8x + 2 + 5  =

-2x  + 7

 

b.

{8x + 12 ] -  [5x - 17 ] =

8x  - 5x  + 12  - (-17)  =

3x + 29

 

c.  (7x) (x - 9)  =  7x * 4x  - 7x * 9    =   28x^2  - 63x

 

2.

2/3 (3x + 14) = 7x + 6     multiply through by 3

2(3x + 14)  = 21x + 18    simplify

6x + 28  =  21x + 18       subtract 6x, 18 from both sides

10 = 15x                         divide both sides by 15 and reduce the fraction

10/15  = x  = 2/3

 

 

cool cool cool

CPhill  Apr 15, 2017

9 Online Users

avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.